Doxycycline increases neurogenesis and reduces microglia in the adult hippocampus - Sultan, Sebastien; Gebara, Elias; Toni, Nicolas (Frontiers in Neuroscience, 2013)
Adult hippocampal neurogenesis results in the continuous formation of new neurons and is a process of brain plasticity involved in learning and memory. Although inducible-reversible transgenic mouse models are increasingly being used to investigate adult neurogenesis, transgene control requires the administration of an activator, doxycycline, with unknown effects on adult neurogenesis. Here, we tested the effect of doxycycline administration on adult neurogenesis in vivo. We found that 4 weeks of doxycycline treatment at doses commonly used for gene expression control, resulted in increased neurogenesis. Furthermore, the dendrites of new neurons displayed increased spine density. Concomitantly, Iba1-expressing microglia was reduced by doxycycline treatment. These results indicate that doxycycline treatment may interfere with parameters of relevance for the use of inducible transgenic mice in studies of adult neurogenesis or brain inflammation.